Myocyte-specific overexpressing HDAC4 promotes myocardial ischemia/reperfusion injury - Ling Zhang; Hao Wang; Yu Zhao; Jianguo Wang; Patrycja M. Dubielecka; Shougang Zhuang; Gangjian Qin; Y Eugene Chin; Race L. Kao; Ting C. Zhao (BMC, 2018)
Abstract Background Histone deacetylases (HDACs) play a critical role in modulating myocardial protection and cardiomyocyte survivals. However, Specific HDAC isoforms in mediating myocardial ischemia/reperfusion injury remain currently unknown. We used cardiomyocyte-specific overexpression of active HDAC4 to determine the functional role of activated HDAC4 in regulating myocardial ischemia and reperfusion in isovolumetric perfused hearts. Methods In this study, we created myocyte-specific active HDAC4 transgenic mice to examine the functional role of active HDAC4 in mediating myocardial I/R injury. Ventricular function was determined in the isovolumetric heart, and infarct size was determined using tetrazolium chloride staining. Results Myocyte-specific overexpressing activated HDAC4 in mice promoted myocardial I/R injury, as indicated by the increases in infarct size and reduction of ventricular functional recovery following I/R injury. Notably, active HDAC4 overexpression led to an increase in LC-3 and active caspase 3 and decrease in SOD-1 in myocardium. Delivery of chemical HDAC inhibitor attenuated the detrimental effects of active HDAC4 on I/R injury, revealing the pivotal role of active HDAC4 in response to myocardial I/R injury. Conclusions Taken together, these findings are the first to define that activated HDAC4 as a crucial regulator for myocardial ischemia and reperfusion injury.